Mechanical responses and mitigation strategies for formation interface slippage during well drilling and hydraulic fracturing - Qi, Hongyan; Zheng, Guoqing; Wei, Xiaochen; Chen, Gang; Liu, Tong; Wang, Wei; Ding, Yi; Tang, Hanlin (Frontiers in Earth Science, 2025)
The frequent incidence of casing failure significantly hampers the efficiency of oil and gas development. Casing failure typically takes place at geological discontinuities, particularly at the formation interface during hydraulic fracturing operations. This occurrence is attributed to the high pressure generated, causing slippage at the formation interface and subsequently resulting in casing shear deformation. In this study, we present a fluid injection-driven slippage model incorporating a discontinuous medium to accurately depict the mechanical responses of the formation interface during the drilling and fracturing operations of a representative well in the Weiyuan gas field, China. The results indicate that interface slip predominantly occurs during the fracturing stage. The slip distance first increases and then decreases as the interface dip angle increases, and it is positively correlated with the permeability of the formation. The maximum interface slip position may not necessarily be at the wellbore due to the influence of the interface dip angle and the permeability difference between both sides of the interface. Furthermore, the maximum slip position tends to move away from the wellbore during fracturing operations. The stress induced by fracturing can alter the stress state near the wellbore, thereby affecting the direction of interface slip. When using low-viscosity fracturing fluid, the interface slip distance reached 0.63 mm, compared to 0.16 mm for high-viscosity fluid. This represents a 75% reduction in slip distance with increased fluid viscosity. Consequently, employing a multi-stage fracturing technique at the intersection of the horizontal wellbore and the discontinuities is recommended. In the early stages of fracturing, a low-viscosity fracturing fluid is suggested to reduce the breaking pressure of the reservoir and efficiently create fractures. In later stages, a high viscosity fracturing fluid can be employed to restrict the interface slip distance and further mitigate the risk of casing failure. This study provides actionable guidance for mitigating casing damage by suppressing interface slip during hydraulic fracturing, demonstrating significant value for field operations.